Extended hyperbolic function method for the (2 +1)-dimensional nonlinear soliton equation - Rehman, Hamood Ur; Awan, Aziz Ullah; Tag-ElDin, ElSayed M.; Alhazmi, Sharifah E.; Yassen, Mansour F.; Haider, Rizwan (Results in physics, 2022)
By employing the extended hyperbolic function method (EHFM), we extract the exact solutions of the (2+1)-dimensional nonlinear soliton equation (SE). A soliton equation is used for investigation of the dynamics of nonlinear waves in plasma physics and fluid dynamics. A various new techniques for finding exact solutions of the (2+1)-dimensional nonlinear SE are satisfactorily acquired with the help of EHFM. The EHFM presents various types of new solutions in the form of dark, singular, periodic, bright solitons and some rational function solutions. In addition, for the physical characterization of the acquired solutions of (2+1)-dimensional SE, some 2-dim and 3-dim plots are drawn. The attained results are novel for the considered equation, and results reveal that the method is concise, direct and competent which can be assembled in other complex phenomena. •By employing the extended hyperbolic function method, the exact solutions of the (2 +1)-dimensional nonlinear soliton equation are obtained.•A soliton equation is used for the investigation of the dynamics of nonlinear waves in plasma physics and fluid dynamics.•For the physical characterization of the acquired solutions of (2+1)-dimensional SE, some 2-dim and 3-dim plots are drawn.•The attained results are novel for the considered equation, and results reveal that the method is concise, direct, and competent which can be assembled in other complex phenomena.